Pengaruh Pengetahuan Audit Dan Skeptisme Profesional Auditor Internal Terhadap Pencegahan Kecurangan - Usman; Mattoasi (Program Studi S1 Akuntansi Jurusan Akuntansi, Fakultas Ekonomi Universitas Negeri Gorontalo, 2021)
The prevention of fraud committed by the Internal Supervisory apparatus of the Regional Government of Gorontalo Province is still relatively low because the audit knowledge and professional skepticism possessed by the internal auditors of the Gorontalo Provincial Government are still very low so that they cannot prevent and detect the occurrence of criminal acts of corruption and cannot even guarantee attendance good governance. This study aims to examine and analyze the effect of internal auditor knowledge on fraud prevention and professional skepticism of internal auditors on fraud prevention in the Regional Government of Gorontalo Province. This study uses an explanatory research method and the type of research used is verification. The types of data used are primary and secondary data and use interval and ordinal scales as measurement scales. Collecting data using survey techniques, whiie the observation unit is the Regional Inspectorate of the Regional Government of Gorontalo Province. The results showed that: (1) Knowledge of internal government audits had an effect on fraud prevention by contributing 45.3% and professional skepticism had an effect on fraud prevention by contributing 56.5% to the local government of Gorontalo province.